The Application of Restorative Justice in The Settlement of Minor Offences - Arta Harianja, Dame; Simamora, Janpatar; Sihotang, Lesson (Greenation Research & Yayasan Global Resarch National, 2024)
The application of restorative justice in resolving minor crimes is increasingly receiving attention in Indonesia as a more humane alternative to the traditional criminal justice system. Resolving minor crimes using a restorative justice approach can be carried out if the conditions are met, such as the perpetrator admitting his actions and showing deep regret, and the victim or his family is willing to forgive. Apart from that, the community also supports deliberation, especially if the act is classified as a minor crime. If these conditions are met, law enforcement officials such as the police can use a restorative justice approach through mediation during the investigation process. The research method used is qualitative with a normative approach where the purpose of this research is to create balance in society. The use of traditional institutions in various regions also greatly supports the implementation of restorative justice, because this model is considered to be in accordance with the values of justice that have long been recognized and implemented in Indonesian society. Thus, restorative justice can be a more inclusive and just solution in resolving minor crimes in Indonesia.